Understanding the socio-technical nexus of Nordic electric vehicle (EV) barriers: A qualitative discussion of range, price, charging and knowledge. (March 2020) - Noel, Lance; Zarazua de Rubens, Gerardo; Kester, Johannes; Sovacool, Benjamin K.
Abstract: Electric vehicles are perceived as a key alternate to internal combustion engine vehicles for a transition to a decarbonized society. However, this transition towards the electrification of transport has not made equal progress globally, and faced several impediments to consumer adoption of EVs across the Nordic region and beyond. While there has been a multitude of reasons provided in the literature, we aim to characterize the barriers that remain to electrification today, as well as their perceived interconnections and futures. To provide insight into this query, the authors conducted 227 semi-structured interviews with transportation and electricity experts from 201 institutions across seventeen cities in Denmark, Finland, Iceland, Norway, and Sweden. The qualitative results and consequent cluster analysis show that common barriers like range, price and charging infrastructure continue to persist, despite technological advancements over the recent years. At the same time, results also show that barriers are highly interconnected and are commonly connected to consumer knowledge and experience. The article concludes with a discussion of policy implications of the findings and potential future research. Highlights: We conducted 227 expert interviews to characterize the barriers of EVs. Experts identified 53 unique categories of barriers of EVs. Range, price, public charging and mental barriers were most commonly identified. We propose a sociotechnical nexus connecting these four barriers. We conclude with future research proposals and policy implications of such a nexus.